Origin and residence time of water in the Lima aquifer - Montoya, Modesto (2014)
The 8 million inhabitants of the coastal city Lima are supplied with water from the Rimac and Chillon rivers and water wells in the Lima aquifer. The history of the Rimac River flow and static level of water in its wells have been correlated to calculate the residence time of water in the aquifer it is recharged by the Rimac River until it reaches a well located 12 km away in the Miraflores District near the sea. The relative abundance of H-2 and O-18 are used to identify the origins of the waters from those wells, and the H-3 and C-14 contents are used to estimate the time after they fall as rain.